Prediction of genomic-enabled breeding values and genome-wide association study for feedlot average daily weight gain in Nelore cattle - Somavilla, Adriana Luiza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Selection for fast growth rates using number of days to achieve specific weights or average weight gain would result in shorter production periods. Maintaining the rate of productivity increasing will demand, among other factors, genetically improved animals in both pasture and feedlot systems. Besides, genomic information could be used to predict genomic-enabled breeding values (GEBVs) earlier in animals' life, which would reduce generation intervals and increase productivity gains. Numerous studies have been conducted in order to identify appropriate methodologies to specific breeds and traits, which will result in more accurate GEBVs. The aim of this study was to compare the prediction accuracy of GEBVs and the ability to identify genomic regions and genes related to average weight daily gain in Nelore cattle, by applying different regression models and genotypes densities datasets. Genomic and phenotypic information of 804 steers born in three season, offspring of 34 bulls, were used to predict GEBVs through three models (Bayesian GBLUP, BayesA and BayesC ), four genotypic densities (Illumina BovineHD BeadChip, TagSNPs, GeneSeek Genomic Profiler High (HDi) and Low (LDi) density indicus) and two adjusted phenotypes. Family structure was accounted by using principal component analysis. Animals were assigned either to training (seasons 1 and 2) or testing (season 3) subsets to perform the cross-validation analysis. Estimates of Pearson correlation, regression coefficients and mean squared errors were used to access accuracy, inflation and bias of the estimated GEBVs, respectively. Genome-wide association study (GWAS) was also performed on above datasets, however, results were compared based on ...

A seleção para taxa de crescimento utilizando o número de dias para atingir determinado peso ou ganho de peso médio resultaria em menores ciclos de produção. Manter o aumento da produtividade exige, entre outros fatores, a utilização de animais melhorados, tanto nos sistemas de pastagem quanto de confinamento. Além disso, as informações genômicas podem ser usadas para predizer os valores genéticos genômicos (GEBVs) mais cedo na vida dos animais, o que reduziria os intervalos de geração e aumentaria os ganhos de produtividade. Inúmeros trabalhos tem sido conduzidos para identificar metodologias apropriadas à determinadas raças e características, o que irá resultar em GEBVs mais acurados. Os objetivos deste estudo foram comparar a acurácia de predição dos GEBVs e a habilidade de identificar regiões genômicas e genes relacionados ao ganho de peso médio diário em bovinos da raça Nelore, pela aplicação de diferentes modelos de regressão e densidades genotípicas. Informações genômica e fenotípica de 804 novilhos nascidos em três safras, filhos de 34 touros, foram utilizadas para predizer GEBVs por meio de três modelos (Bayesian GBLUP, BayesA e BayesC ), quatro densidades genotípicas (Illumina BovineHD BeadChip, TagSNPs, GeneSeek indicus de alta (HDi) e baixa (LDi) densidades) e dois fenótipos ajustados. A estrutura de família foi considerada por meio da análise de componentes principais. Os animais foram distribuídos em subconjunto de treinamento (safras 1 e 2) ou validação (safra 3) para realização da análise de validação cruzada. Estimativas de correlação de Pearson, coeficientes de regressão e erro quadrado médio foram usados para avaliar acurácia, inflação e viés dos GEBVs estimados, respectivamente. O estudo de associação ampla do genoma (GWAS) também foi realizado nos mesmos conjuntos de dados, entretanto, os resultados foram comparados com...
Keywords: Bovino; Teoria bayesiana de decisão estatistica; Nelore (Zebu); Crescimento; Genômica; Genetica animal; Genomics